A qualitative case study on experiences of universities and industries linkages in Nigeria - Aloysius, Odigbo Ikechukwu; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2019)
Experience is seen as a fact or evidence of engaging in doing something e.g. learned a lesson in the classroom, work engagement experience and painful experiences such as a scene of difficulties in work-related activity or event. The experiences of the industries in the employability of graduates are widely explored to build on descriptive research approach geared to examine the employability skills close to the Nigerian context and linkages between universities-industries. The National Youths Service Corps experiences help graduates to know various kinds of industrial practices, work ethics, and integrate the importance of theoretical knowledge gained from the university and incorporate into industrial practice. Extra curricula training experience in university-industry linkages help graduates to perform very effectively and efficiently in some special skills. Internship and modern uses of technological experience help to advance career development in a particular environment and help to know the newest technologies relevant to the industry. This study recommends that universities and industries should enhance linkages among management boards, foster strategic plans and directions, collaborates on research, and create policies for the effective governance of industries linkages for promoting an important institutional approach to build industries linkages. Finally, Universities should improve in various strategies such as offering work experience, work-related learning and employability skills modules, ready for work events, as well as involving industry employers in course design and delivery.